Creative Cooperation of Subjects of the Educational Process in the Context of Musical Activity - Andreiko, Oksana; Savchenko, Regina; Vasilenko, Lyudmila; Khizhna, Olga; Savchenko, Yuliya (Journal of History Culture and Art Research, 2019)
This article discusses the creative cooperation of subjects of the musical-educational process as a practical mechanism for the humanization of music education, which allows establishing “subject-subject” relations between the teacher/lecturer and pupils/students and contributes to the disclosure of the creative potential of all participants in the musical-educational process. The analysis of the scientific literature on the idea of cooperation in the history of education, musical pedagogy in retrospective and modern dimensions is presented. The main contradictions of its solution at the present stage are determined. The purpose of this article is to substantiate the ideas of pedagogy of cooperation in the context of the humanization of music education. The main methods used in the study are comparative, analytical, historical, system-structural. It is concluded that the artistic and pedagogical process in terms of music education allows establishing conditions for the creative cooperation of the teacher and the student.